A universal approach to crosslinked hierarchical polymer multilayers as stable and highly effective antifouling coatings - Wei, Qiang (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.